Sosialisasi Pencegahan Kebakaran di Selili Kelurahan Manggar RT 42 Kecamatan Balikpapan Timur - Nadi Hernadi Moorcy; Felix Kitto Liman Lim; Iswandi Iswandi; Dinda Dita Rahayu; Latifatul Aulia; Annisa Annisa; Nabillah Choirun Nisa; Farhan Budiman; Chandra Aditya W.; Alfian Ersar Anggara; Arsenius Darmawan Orlando (Abdimas Universal, 2024)
Fire disasters are one of the disasters that often occur in the wider community, be it office environments, residences, or other places of activity. One of them is in densely populated environments, the occurrence of fire disasters themselves has many factors, but in general these fire disasters occur in caused by human factors, which are none other than negligence, such as using electrical loads that exceed the power capacity and forgetting to turn off tools that are sources of heat, such as stoves and irons. One effort to reduce the occurrence of this fire disaster is by providing Fire Prevention Socialization to the surrounding community. The aim of this service itself is to provide insight into how to prevent and deal with fire disasters, which is carried out using lecture methods and direct simulation methods by the material givers. By carrying out this socialization, it is hoped that the surrounding community will be able to apply the methods taught during the simulation. if a fire disaster occurs in the surrounding area.